Pengaruh Disiplin Kerja, Pengalaman Kerja, Dan Gaji Terhadap Kinerja Karyawan Toko Murah Rejeki Semarang - Ninda Natasya Risnawati; Ida Martini Alriani (Jurnal Riset dan Inovasi Manajemen, 2024)
The purpose of this research is to determine the influence of work discipline, work experience, and salary on the performance of Toko Murah Rejeki Semarang employees. The population in this study were 40 employees of the Rejeki Cheap Shop Semarang. This sample was determined using a saturated sampling technique. The number of samples used in this research was 40 employees. This research data analysis tool uses multiple linear regression. The research results show that work discipline has a positive effect on employee performance. This is shown by the tcount value being greater than the t table, namely 2.032 > 1.688, with a significance value of 0.044 < 0.05 (significant). Work experience has a positive effect on employee performance. This is shown by the tcount value being greater than the t table, namely 2.080 > 1.688, with a significance value of 0.042 < 0.05 (significant). Salary has a positive effect on employee performance. This is shown by the tcount value being greater than the t table, namely 2.914 > 1.688, with a sig value. equal to 0.006 < 0.05 (significant).